How do you solve x(x + 9) = 0?

3 Answers
Nov 10, 2015

x = 0
x = -9

Explanation:

x(x+9) = 0 is the same as (x+0)(x+9) = 0.
So, we know that x + 0 = 0 and that x + 9 = 0.
So, we solve both for x, and we get x = 0 and x = -9.

Hope it Helps! :D .

Nov 10, 2015

Find out when the factors are equal to zero

Explanation:

So what we have here is a equation with two factors; x and (x+9).

To make the expression x(x+9) = 0, at least one of the factors has to be 0. This means that either:

x = 0

or

x + 9 = 0 to x = -9

Nov 10, 2015

x=0 or x=-9.

Explanation:

A product of real numbers is zero if and only if one of the two factors is zero. In your case, the two factors are x and x+9.

So, one possible case is that the product is zero because x is zero.

A second case is that x+9=0. To solve this equation, simply subtract nine by both terms:

x cancel(+9)cancel(-9)=0-9, and thus x=-9

So, the two values x=0 and x=-9 annihilate one of the factors each, and so the annihilate the whole product.